2005
DOI: 10.1093/bja/aei143
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin, interleukin 6 and systemic inflammatory response syndrome (SIRS): early markers of postoperative sepsis after major surgery

Abstract: PCT and IL-6 appear to be early markers of subsequent postoperative sepsis in patients undergoing major surgery for cancer. These findings could allow identification of postoperative septic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
2
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(166 citation statements)
references
References 25 publications
9
150
2
5
Order By: Relevance
“…In previous studies, a simple plasma measurement served as the basis to define the status of the immune response during ongoing sepsis (25) and patients are considered hyperinflammatory if proinflammatory cytokines are found at elevated levels. We now report that the early phase of lethal sepsis is characterized by the overexpression of both proinflammatory as well as anti-inflammatory cytokines.…”
mentioning
confidence: 99%
“…In previous studies, a simple plasma measurement served as the basis to define the status of the immune response during ongoing sepsis (25) and patients are considered hyperinflammatory if proinflammatory cytokines are found at elevated levels. We now report that the early phase of lethal sepsis is characterized by the overexpression of both proinflammatory as well as anti-inflammatory cytokines.…”
mentioning
confidence: 99%
“…When the body is subjected to surgical stress, levels of inflammatory cytokines such as TNF-␣, IL-1␤, IL-6 and IL-8 are known to increase, while at the same time, levels of anti-inflammatory cytokines such as IL-4 and IL-10 are also elevated. From the perspective of measurement sensitivity, IL-6 in the plasma can be easily detected after surgery, and is frequently used as a SIRS marker 3,7,11,[15][16][17][21][22][23]27,31) . Studies have shown that plasma levels of IL-6 are significantly higher in patients with postoperative SIRS 7,20,22,31) , remain high in deceased patients with SIRS 7,20) , and closely reflect degree of surgical stress 4) .…”
Section: Changes In Cytokinesmentioning
confidence: 99%
“…The signs of systemic inflammatory response syndrome (SIRS) were identified if the patient had a body temperature <35.6°C or >38.3°C, tachycardia >90 beats per min (bpm), ventilatory frequency >20 bpm or Pa CO2 <4.27 kPa (unless the patient was mechanically ventilated), a white cell count ≥12×10 9 /l or ≤4×10 9 /l, or >10 % immature neutrophils (bands), as previously described [10]. Sepsis was defined when the patients had SIRS associated with infection according to Bones' criteria [11].…”
Section: Experimental Assignmentmentioning
confidence: 99%
“…Infection was identified if microbiological cultures obtained from the patients at possible sites of infection were positive (proven infection) or if clinical signs of infection were evident. Patients were assigned into two groups: the sepsis group (patients with sepsis, severe sepsis [10], and septic shock [10]) and the control group (patients with SIRS or no evidence of sepsis).…”
Section: Experimental Assignmentmentioning
confidence: 99%